Study on the Residual Stress Relieving Mechanism of C/C Composite-Nb Brazed Joint by Employing a Structurally Optimized Graphene Reinforced Cu Foam Interlayer - Li, Hongliang; Wang, Zeyu; Butt, Hassaan Ahmad; Ye, Maocheng; Chen, Hao; Zhao, Tianmo; Li, Manni; Ma, Qiang; Lei, Yucheng (Frontiers in Materials, 2021)
Cu foam has previously been investigated and verified to be an excellent interlayer candidate for relieving high residual stress within C/C composite-Nb brazed joints. However, the optimized geometric structure of Cu foam for brazing has never been properly investigated since it was always employed as a reactant for acquiring homogeneous distribution of the interfacial structures in the brazed joints. In this work, graphene reinforced Cu foam composite (G-Cuf) interlayers were used for brazing C/C composite and Nb. Through the protection effect of graphene on the Cu foam substrate, the impact of porosity and thickness of a structurally intact Cu foam on the joint structure and properties were investigated by finite elemental analysis as well as through experimental studies. By introducing a G-Cuf interlayer with an optimized porosity of 90% and thickness of 0.15 mm, the shear strength of the C/C composite-Nb brazed joint reached 45 MPa, which is 3.5 times higher than that of the joint brazed directly without an interlayer. The strain energy of the brazed joint assisted by G-Cuf interlayer reduced from as high as 10.98×10-6 J to 6.90×10-6 J, suggesting that the residual stress was effectively mitigated.